SCIENTIFIC DISSEMINATION AND CTS: A YOUTUBE VIDEOS STUDY ON ENVIRONMENTAL THEMATICS - Melo, Rafael Augusto; Pereira, Brenda Braga; Menezes, Isadora Moutinho Carvalho ângelo; Moreira, Diego Ferreira (Cadernos de Educação Tecnologia e Sociedade, 2020)
This research aimed to analyze the articulations between Science, Technology and Society in Youtube videos, which approached environmental issues. The videos were chosen from channels that called themselves scientific dissemination, and that owned the ScienceVlogs "seal of quality". It were selected the Pirula Channel, the Slow Channel and Common Point, due they exhibited Nature Sciences information and they had videos about environmental impacts. From the video selection were carried out two analysis. The first one was a mapping of the number of views, of the number of subscribers and also about some features of these channels, such as language, target audience and environmental theme. The second analysis verified how the features of Science, Technology and Society appeared in each of the videos. The Science category was divided in three clusters: Interdisciplinar, Science’s Nature and Content-focused. It was realized the videos approach were mostly content-focused. There were few interdisciplinary videos. In Science’s Nature cluster there were scientific work features and some science point of views, mainly from the authors themselves. In the Technology category, two groups were created: Apparatus and Development. It was verified technology’s features related with the use of them as a tool or their development over time. The both ways were used to exemplify certain content. Only two videos were about features related with our referential about non-neutrality of technology. In the Society category were created three groups: Politics, Economy and Articulation with daily life, which were relevant features to CTS research, since it can contribute to the development of autonomy in individuals.